2020
DOI: 10.1186/s12872-020-01657-0
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the prevalence of measures associated with hypertension among Iranian adults according to classification by ACC/AHA guideline 2017

Abstract: Background: Different definitions have been proposed to categorize hypertension. We aimed to investigate the difference in prevalence of measures associated with hypertension according to the American College of Cardiology/American Heart Association (ACC/AHA) criteria versus Joint National Committee 7 (JNC7) criteria. Methods: We analyzed the data of 10,000 participants of Yazd Health Study (YaHS) aged 20-69 years. Blood pressure was measured three times with standard protocol defined by ACC/AHA. Prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
1
10
1
Order By: Relevance
“…Although there was some heterogeneity in prevalence across study centers, the application of the ACC/AHA guideline uniformly led to increase in relative prevalence (by 63.7%) and decrease in relative awareness (37.3%), treatment (38.7%), control among hypertensive adults (63.4%), and control among treated adults (39.5%). Yet, the increase in prevalence observed in our study was still lower than previous studies in Iran, which reported a more than a twofold higher prevalence based on the ACC/AHA guideline 16 18 . Less than twofold increases were also observed in other countries 10 , 11 , 19 , 20 .…”
Section: Discussioncontrasting
confidence: 96%
“…Although there was some heterogeneity in prevalence across study centers, the application of the ACC/AHA guideline uniformly led to increase in relative prevalence (by 63.7%) and decrease in relative awareness (37.3%), treatment (38.7%), control among hypertensive adults (63.4%), and control among treated adults (39.5%). Yet, the increase in prevalence observed in our study was still lower than previous studies in Iran, which reported a more than a twofold higher prevalence based on the ACC/AHA guideline 16 18 . Less than twofold increases were also observed in other countries 10 , 11 , 19 , 20 .…”
Section: Discussioncontrasting
confidence: 96%
“…Diabetes was defined as fasting blood glucose equal to or higher than 126 mmol/L, or was on medication for raised blood glucose, or had a history with the diagnosis of diabetes [ 31 ]. HTN was defined as systolic blood pressure (SBP) ≥130 mmHg, and /or a diastolic blood pressure (DBP) ≥80 mmHg according to the ACC/AHA guideline, a prior diagnosis of hypertension by a health professional indicating that one had high BP or used antihypertensive drugs [ 32 ]. CVD includes the history of myocardial infarction or/and stroke or/and cardiac ischemia.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the increase in prevalence observed in our study was still lower than previous studies in Iran, which reported a more than a 2-fold higher prevalence based on the ACC/AHA guideline. [16][17][18] Less than 2-fold increases were also observed in other countries. 10,11,19,20 The results of our study showed that a total of 24 312 adults who were previously classified in the category of "pre-hypertension", were shifted to stage 1 of hypertension based on the ACC/AHA 2017 guideline.…”
Section: Discussionmentioning
confidence: 77%